Optimum network reconfiguration based on maximization of system loadability using continuation power flow theorem - Aman, M.M.; Jasmon, G.B.; Bakar, A.H.A.; Mokhlis, Hazlie (Elsevier, 2014)
This paper presents a new algorithm for network reconfiguration based on maximization of system loadability. Bifurcation theorem known as Continuation Power Flow (CPF) theorem and radial distribution load flow analysis are used to find the maximum loadability point. Network reconfiguration results are also compared with existing technique proposed in literature. In the proposed method, to find the optimum tie-switch position, a Discrete Artificial Bee Colony (DABC) approach is applied. Graph theory is used to ensure the radiality of the system. The proposed algorithm is tested on 33-bus and 69-bus radial distribution networks, each having 5-tie switches. The result shows that using the proposed method the kVA margin to maximum loading (KMML) increases, overall voltage profile also improved and the distribution system can handle more connected load (kVA) without violating the voltage and line current constraints. Results further show that the voltage limit is an important factor than the line current constraints in adding further load to the buses.